Tingkat Kemampuan Servis Bawah Bola Voli (Studi Empiris pada Siswa Kelas VIII A SMP Muhammadiyah 05 Surakarta) - Astuti, Winata Aji; Jariono, Gatot; Sudarmanto, Eko (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the level of ability to serve under volleyball in class VIII A students of SMP Muhammadiyah 05 Surakarta. The method used is descriptive research with a population of all students in class VIII A, totaling 18 female students, but 2 students were absent in data collection. Data collection techniques were carried out using tests. The instrument used was the 1969 AAHPER serving accuracy test . The results of this study indicate that the level of volleyball lower serve ability in class VIII A students of SMP Muhammadiyah 05 Surakarta that of the 16 students who took the volleyball lower serve ability test, 8 students were in the “less” category with a percentage of 50%. then the “sufficient” category was 3 students with a percentage of 18.8%, the “excellent” category was 3 students with a percentage of 18.8%, the “good” category was 2 students with a percentage of 12.5%, and the last category “very poor” was 0 students with a percentage of 0%. The results of this study indicate that the level of ability to serve under volleyball in class VIII A students of SMP Muhammadiyah 05 Surakarta is classified in the “less” category. Conclusion: Most students have not yet reached the expected proficiency standards in mastering the basic underhand serve technique, which is a fundamental volleyball technique for starting the game and influencing the success of the team's strategy in playing volleyball. Keywords: Ability, Lower Serve, Volleyball